Working for God? Evidence from a Change in Financing of Nonprofit Health Care Providers in Uganda - Reinikka, Ritva; Svensson, Jakob (2012)
What motivates religious nonprofit health care providers? This paper uses a change in financing of nonprofit health care providers in Uganda to test two theories of organizational behavior. We show that financial aid leads to more laboratory testing, lower user charges, and increased utilization. These findings are consistent with the view that religious nonprofit providers are intrinsically motivated to serve (poor) people and that these preferences matter quantitatively.